Xenopus Pkdcc1 and Pkdcc2 are two new tyrosine kinases involved in the regulation of JNK dependent Wnt/PCP signaling pathway - Belo, José (2017)
This work was supported by research grants from the Fundacao Ciencia e Tecnologia - IP (http://www.fct.pt/index.phtml.pt), and from IBB/CBME, LA to J. A. Belo in the frame of Projects ref degrees PTDC/BIA-BCM/69912/2006 and Pest-OE/EQB/LA0023/2013. M. Vitorino, A. C. Silva and J. M. Inacio are recipients of FCT post-doc fellowships.